COMPARATIVE DIAGNOSIS OF Entamoeba histolytica And Giardia lamblia AMONG CHILDREN WITH DIARRHOEA AND THEIR ASSOCIATED RISK FACTORS IN SOME SELECTED HOSPITALS IN ADAMAWA STATE, NIGERIA - Kadabiyu, Ganabuto Jones (FUDMA Journal of Sciences, 2026)
A cross-sectional hospital-based study was conducted to determine the prevalence of intestinal Protozoans and other parasites among diarrheal children in some selected hospitals from November 2024 to December 2025. Stool and blood samples were obtained and examined microscopically (saline wet mount, formol-ether concentration), and serologically using Enzyme-Linked Immunosorbent Assay (ELISA), to identify the antigens of G. lamblia and E. histolytica. Questionnaires were also administered to obtain socio-demographic information and risk factors.  Data collected were analysed using R-statistical software, chi-square tests, and risk factors were identified through multivariate logistic regression, with statistical significance set at p
Keywords: Entamoeba histolytica; Giardia lamblia; Seroprevalence; Diarrhoea; Children; Risk Factors; Nigeria